Mobilization in crisis – demobilization in peace: protagonists of competing national movements in border regions - Martin Klatt (Studies on National Movements, 2019)
Border zones are characteristic for being the site of competing national movements’ struggle on a territory and its population: a population did not only have to awaken to a nationality, but also to the ‘correct’ nationality. Studying national protagonists of competing national movements in border regions therefore promises solid evidence of the reasons underpinning national movements’ success and/or failure to attract the masses.